The Possible Influence of Non-synonymous Point Mutations within the FimA Adhesin of Non-typhoidal Salmonella (NTS) Isolates in the Process of Host Adaptation - Alshalchi, Sahar; Hayer, Shivdeep S.; An, Ran; Munoz-Aguayo, Jeannette; Flores-Figueroa, Christian; Nguyen, Ryan; Lauer, Dale; Olsen, Karen; Alvarez, Julio; Boxrud, David; Cardona, Carol; Vidovic, Sinisa (Frontiers in Microbiology, 2017)
Non-typhoidal Salmonella (NTS) remains a global pathogen that affects a wide range of animal species. We analyzed a large number of NTS isolates of different host origins, including Salmonella Heidelberg (n=80, avian), S. Dublin (50, bovine), S. Typhimurium var 5- (n=40, porcine), S. 4,5,12,:i:- (n=40, porcine), S. Cerro (n=16, bovine), and S. Montevideo (n=14, bovine), using virulence profiling of the bcfC, mgtC, ssaC, invE, pefA, stn, sopB, and siiE virulence-associated genes, a biofilm production assay, pulsed field gel electrophoresis, and the full-length sequencing of the fimA (adhesin) and iroN (receptor) genes. We determined a key amino acid substitution, A169 (i.e. threonine changed to alanine at position 169), in the FimA protein that changed ligand affinity of FimA towards N-acetyl-D-glucosamine. This finding clearly indicates the important role of non-synonymous single nucleotide polymorphism (nsSNPs) in adhesin functionality that may impact the host tropism of NTS. This nsSNP was found in S. Heidelberg and S. Cerro isolates. Although this was not the case for the IroN receptor, the phylogeny of this receptor and different host origins of NTS isolates were positively correlated, suggesting existence of specific host immune selective pressures on this unique receptor in S. enterica. We found that pefA, a gene encoding major fimbrial subunit, was the most-segregative virulence factor. It was associated with S. Heidelberg, S. Typhimurium var 5- and S. 4,5,12,:i:- but not with the rest of NTS strains. Further, we observed a significantly higher frequency of non-biofilm producers among NTS strains that do not carry pefA (42.5%) compared to S. Heidelberg (2.5%) and S. Typhimurium var 5- (7.5%) and S. 4,5,12,:i:- (0%). This study provides new insights into the host adaptation of avian and mammalian NTS isolates that are based on the bacterial antigens FimA and IroN as well as the interrelationships between host adaptation, overall genetic relatedness, and virulence potential in these NTS isolates.